2020
DOI: 10.1108/jarhe-05-2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the influence of aesthetic experience on the innovative behaviors of Thai students and Chinese international students

Abstract: PurposeThe purpose of this study aims to understand if there are any differences in the influence of aesthetic experience and creative self-efficacy on innovative behaviors of Thai students and Chinese international students and whether creative self-efficacy has a mediating effect between aesthetic experience and innovative behavior.Design/methodology/approachThree Thai universities with Chinese international students were selected through purposive sampling. There were 329 valid responses, consisting of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Kleebbua and Lindratanasirikul (2021) also found that the learning climate has a significant direct effect on students' innovative behavior (Chang and Yang, 2012). Lussier (2010) stated that the acquisition of aesthetic experience by students is positive for the development of innovative behavior (Chang and Jaisook, 2021). After an individual's digestion, accumulation, and internalization of aesthetic experience, it may boost one's confidence to accept challenges and becomes an essential factor for the emergence of creative behaviors (Davies et al, 2009).…”
Section: School Climate Aesthetic Experience and Innovative Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Kleebbua and Lindratanasirikul (2021) also found that the learning climate has a significant direct effect on students' innovative behavior (Chang and Yang, 2012). Lussier (2010) stated that the acquisition of aesthetic experience by students is positive for the development of innovative behavior (Chang and Jaisook, 2021). After an individual's digestion, accumulation, and internalization of aesthetic experience, it may boost one's confidence to accept challenges and becomes an essential factor for the emergence of creative behaviors (Davies et al, 2009).…”
Section: School Climate Aesthetic Experience and Innovative Behaviormentioning
confidence: 99%
“…To be a part of an aesthetic experience, beauty must transcend from its extrinsic to intrinsic values ( Marković, 2012 ). In other words, ugly things can also elicit aesthetic experience ( Eco, 2007 ), and good can be found in bad things ( Chang and Jaisook, 2021 ). Thus, aesthetic experience is not only about viewing extrinsic beauty but also includes personal reflections, attitudes, and moral values ( Garrison, 1997 ; Eaton, 2001 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows that studies on the relationship of CSE with creativity/creativity indicators (n=18) and individual/environmental factors (n=16) have the highest frequency among all others (total=88). The former group examined the relationships between CSE and creativity (Broekhoven at al., 2020;Haase et al, 2018); CSE and creative performance (Chang & Jaisook, 2020;Lemons, 2010;Li & Wu, 2011;Paek et al, 2016;Park et al, 2021;Reiter-Palmon et al, 2012;Royston & Reiter-Palmon, 2019); CSE and creative thinking (Anderson & Graham, 2021;Kharkhurin, 2017 (Beghetto, 2009). At the same While examining the studies on personal characteristics, we found that Karwowski (2016) analyzed the changes occurred in 6 months (short-term) and 20 months (medium-term) periods in CSE and Review of the studies that examined the relationships between CSE and environmental factors revealed that studies investigated the effects of parents (Gralewski & Jankowska, 2020;Liang & Yuan, 2020), peers (Karwowski, 2015;Liu et al, 2016), and personenvironment fit (Cayirdag, 2016).…”
Section: Research Issues/themesmentioning
confidence: 99%